2008
DOI: 10.1124/mol.108.049502
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin Inhibits Matrix Metalloproteinase-9 Expression through Down-Regulation of Nuclear Factor-κB Signaling Pathway in Human Hepatocellular Carcinoma Cells

Abstract: Vanillin has been reported to exhibit anti-invasive and antimetastatic activities by suppressing the enzymatic activity of matrix metalloproteinase-9 (MMP-9). However, the underlying mechanism of anti-invasive activity remains unclear so far. Herein we demonstrate that vanillin reduced 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced MMP-9 gelatinolytic activity and suppressed cell invasion through the down-regulation of MMP-9 gene transcription in HepG2 cells. Vanillin significantly reduced the 6.6-fold inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…A subsequent study further demonstrated the anti-inflammatory effect of vanillin during a treatment of inflammatory bowel diseases where vanillin prevented trinitrobenzene sulfonic acid-induced colitis and reduced established colitis in mice (73). Finally, vanillin decreased angiogenesis and showed protected against hepatocarcinogenesis (74), while also displaying anti-cancer properties as evidenced by its inhibition of matrix metalloproteinase-9 and P13K gene expression levels and regulation of the cell cycle and apoptosis in HepG2 cells, through which it suppressed the invasion and migration of cancer cells (66,75,76). Syringaldehyde is a naturally occurring aromatic aldehyde (Fig.…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 99%
“…A subsequent study further demonstrated the anti-inflammatory effect of vanillin during a treatment of inflammatory bowel diseases where vanillin prevented trinitrobenzene sulfonic acid-induced colitis and reduced established colitis in mice (73). Finally, vanillin decreased angiogenesis and showed protected against hepatocarcinogenesis (74), while also displaying anti-cancer properties as evidenced by its inhibition of matrix metalloproteinase-9 and P13K gene expression levels and regulation of the cell cycle and apoptosis in HepG2 cells, through which it suppressed the invasion and migration of cancer cells (66,75,76). Syringaldehyde is a naturally occurring aromatic aldehyde (Fig.…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 99%
“…The observation that the widely-used natural flavouring agent vanillin (4-hydroxy-3-methoxybenzaldehyde; compound 10, Table I) behaves as an NFĸB inhibitor in both in vitro and in vivo preclinical models (34)(35)(36) of a small panel of aromatic aldehydes, including vanillin, to suppress chemotherapy-induced NFĸB activity, and to inhibit tumour cell growth. Even though, surprisingly, vanillin was ineffective in modulating NFĸB activity under our experimental conditions, six out of the 10 tested aldehydes (namely compounds 1, 3, 5, 6, 7 and 9) were effective in suppressing NFĸB induction by the anticancer drug doxorubicin in cultured A375 human melanoma cells (Table I), with o-vanillin, a naturally occurring isomer of vanillin (40), being the most potent compound (Table I, and Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…Although unable to suppress primary tumour growth itself, vanillin was found to exert anti-metastatic activity in the 4T1 mouse mammary carcinoma spontaneous metastasis model, and to inhibit tumour cell invasion and migration in vitro (32). More recently, vanillin was found to inhibit angiogenesis in a chick chorioallantoic membrane assay (33), and to suppress NFĸB activation induced by various inflammatory stimuli including tumour necrosis factorrelated apoptosis-inducing ligand, tumour necrosis factor α (34), trinitrobenzene sulfonic acid (35), and 12-Otetradecanoylphorbol-13-acetate (36). The suppressive effect of vanillin on NFĸB activity may be a major mechanism underlying its anti-invasive, anti-metastatic and antiangiogenic properties, and offers potential for developing novel anticancer agents.…”
mentioning
confidence: 99%
“…In the transwell migration assay, we found that downregulation of AIB1 decreased the ability of cells to migrate through the membrane (Figure 4a). In the transwell invasion assay, We used 12-O-tetradecanoylphorbol-13-Acetate (TPA), an activator of protein kinase C that can promote HepG2 cell invasion via MMP-9 induction (Liang et al, 2009), to induce cell invasion and found that downregulation of AIB1 significantly decreased the number of cells that penetrated through the Matrigel-coated membrane (Figure 4b). These results indicate that the invasive potential of HCC cells is significantly reduced by AIB1 knockdown.…”
Section: Downregulation Of Aib1 Reduces Hcc Cell Migration and Invasionmentioning
confidence: 99%